Caracterização e composição química do material particulado grosso (MP10) no centro da cidade de São Carlos (SP) - Alexandrina, Eduardo Carlos (Universidade Federal de São Carlos, 2015)
Coarse particulate matter with aerodynamic diameter smaller than 10μm (PM10) have long been considered as air pollutants associated with health issues. They penetrate into the upper respiratory tract, causing respiratory problems such as worsening of asthma. The aim of this study was to determine and quantify the distribution of chemical elements in the PM10 particulate matter present in the atmosphere of the city of Sao Carlos (Sao Paulo). Samples were collected daily for a period of 23h and 30 minutes, from April 16, 2014 to April 16, 2015. A high-volume sampler (AGV-PM10) with micro quartz and fiber glass filters were used. The filters were subjected to gravimetric analysis to obtain the mass of PM10 and were then analyzed by energy dispersive X-ray fluorescence and Laser Induced Breakdown Spectroscopy to identify and quantify the chemical composition of the samples. The highest average concentration during twelve-month period was 70.41μg/m³ (August, 2014) and the smallest was 22.59μg/m³ (January, 2015). The annual arithmetic average found for the twelve months period was 42.71μg/m³. If compared with annual arithmetic average limit of 40μg/m³, established by CETESB, the value is slightly above and below 50 μg/m³ (CONAMA). If we consider the limit established by the World Health Organization (WHO), which is 20μg/m³, this value is much higher than recommended. The chemicals elements found were characteristic of urban areas
Keywords: Material particulado; Amostrador de grandes volumes; Fluorescência de raio X; LIBS; Inhalable particulate matter (PM10); High volume sampler (Hi-vol); Fluorescence X-ray energy dispersive (ED-XRF); Laser induced breakdown spectroscopy (LIBS); ENGENHARIAS::ENGENHARIA QUIMICA